Does co-supplementation with beetroot juice and other nutritional supplements positively impact sports performance?: a systematic review - Ferrada-Contreras, E.; Bonomini-Gnutzmann, R.; Jorquera-Aguilera, C.; MacmiIlan Kuthe, N.; Peña-Jorquera, H.; Rodríguez-Rodríguez, F. (Nutrients, 2023)
In the pursuit of enhanced athletic prowess in different disciplines, athletes constantly look for strategies to increase their physical performance, encompassing technical skills and dietary components, which inevitably, in most cases, include the incorporation of sports supplements. In recent years, there has been an increase in the number of athletes using ergogenic aids. In this context, scientific evidence must play a prominent role in either endorsing or warning against the use of these products, ensuring the preservation of health while promoting the theoretically established positive benefits. In this vein, beetroot juice (BJ) stands out as a key supplement as an ergogenic aid to improve sports performance, given its demonstrated influence on both aerobic and anaerobic exercise. However, despite widespread global demand, there remains a lack of understanding regarding the potential synergistic effects of combining BJ with other supplements. Consequently, our study aims to determine whether the combination of BJ with another nutritional supplement can enhance its beneficial effects and, therefore, optimize physical performance in humans. A comprehensive literature search was conducted in two major databases—Web of Science and PubMed—from 1 January 2018 to 29 January 2023, using specific keywords. After the exclusion criteria, six articles were selected for analysis. Therefore, our study shows that the effectiveness of combining BJ with another supplement mainly depends on the duration of the chronic intervention, which is where the greatest benefits have been observed.